Microplastics Removal Strategies in Aquatic Environments - Widiyanto, Edhi; Istirokhatun, Titik; Andarani, Pertiwi; Susanto, Heru; Desiriani, Ria; Apriliana, Pamella (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2025)
Microplastics (MPs) have been globally detected in aquatic environments. The abundance of MPs contributed to the negative effects on aquatic ecosystems. Thus, it’s critical to create effective solutions for removing MPs from water. In this review, we compared several methods, including physical, physicochemical, and biological approaches, towards membrane filtration. The physical filtration technology is the simplest way in comparison with other methods. However, the removal ability of physical filtration against smaller MPs than 20 ?m becomes a crucial concern. Then, the other option is an adsorption method. Although the adsorption option is an inexpensive method, the undesirable aspect during adsorbent usage may not be environmentally friendly in aquatic systems. The similar problem is also demonstrated by chemical approaches in terms of coagulation and electrocoagulation treatment. Consequently, the biological methods were found to be less toxic to the environment. Even though it provides safe conditions to the environment, the biological approach needs a long time to degrade MPs. To overcome their disadvantages, the membrane technology offers efficient removal of MPs and no addition of chemical usage. However, the main point to pay attention to is that each technology has benefits and drawbacks. Therefore, the application of multiple technologies for MPs removal is considered.